Beiträge zur Kenntnis der afrikanischen Popillia-Arten (Coleoptera: Lamellicornia, Melolonthidae, Rutelinae). 1. Über Popilia dorsofasciata Fairmaire und ihre Verwandten. - Machatschke, Johann W. (Contributions to Entomology = Beiträge zur Entomologie, 1960)
The author discusses the phylogeny of the relationship of Popillia dorsofasciata (Popillia macularia, laetans, nyassica, ertli and ohausi) and describes as new the hitherto misinterpreted races Popillia ertli maculata n. ssp., P. nyassica puella n. ssp., P. ohausi makondana n. ssp., P. ohausi rufopyga n. ssp., P. ohausi vicina n. ssp. Nomenclatural Actsmaculata Machatschke, 1960 (Popillia ertli), sspec. n.puella Machatschke, 1960 (Popillia nyassica), sspec. n.makondana Machatschke, 1960 (Popillia ohausi), sspec. n.rufopyga Machatschke, 1960 (Popillia ohausi), sspec. n.vicina Machatschke, 1960 (Popillia ohausi), sspec. n.